FORMATION OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHERS OF TECHNOLOGY IN STUDY ELECTRICAL MEASURING INSTRUMENTS - Yu.V. Nedashkovskiy (Academy of Cognitive and Natural Sciences, 2008)
Brought methodology of learning the students to bases an algorithm of pedagogical problems for technology of automation, in particular buildings montage schemes on the base and performing the problems with technological contents and with use the between discipline relationships.